Roles of I(f) and intracellular Ca2+ release in spontaneous activity of ventricular cardiomyocytes during murine embryonic development. Issue 8 (12th June 2013) - Wang, Peng; Tang, Ming; Gao, Linlin; Luo, Hongyan; Wang, Guoping; Ma, Xue; Duan, Yaqi
Abstract In recent years, the contribution of I(f), an important pacemaker current, and intracellular Ca2+ release (ICR) from sarcoplasmic reticulum to pacemaking and arrhythmia has been intensively studied. However, their functional roles in embryonic heart remain uncertain. Using patch clamp, Ca2+ imaging, and RT‐PCR, we found that I(f) regulated the firing rate in early and late stage embryonic ventricular cells, as ivabradine (30 µM), a specific blocker of I(f), slowed down action potential (AP) frequency. This inhibitory effect was even stronger in late stage cells, though I(f) was down‐regulated. In contrast to I(f), ICR was found to be indispensable for the occurrence of APs in ventricular cells of different stages, because abolishment of ICR with ryanodine and 2‐aminoethoxydiphenyl borate (2‐APB), specific blockers of ryanodine receptors (RyRs) and inositol trisphosphate receptors (IP3Rs), completely abolished APs. In addition, we noticed that RyR‐ and IP3R‐mediated ICR coexisted in early‐stage ventricular cells and RyRs functionally dominated. While at late stage RyRs, but not IP3Rs, mediated ICR. In both early and late stage ventricular cells, Na‐Ca exchanger current (INa/Ca) mediated ICR‐triggered depolarization of membrane potential and resulted in the initiation of APs. We also observed that different from I(f), which presented as the substantial component of the earlier diastolic depolarization current, application of ryanodine, and/or 2‐APB slowed the late phase of diastolic depolarization. Thus, we conclude that in murine embryonic ventricular cells I(f) regulates firing rate, while RyRs and IP3Rs (early stage) or RyRs (late stage)‐mediated ICR determines the occurrence of APs. J. Cell. Biochem. 114: 1852–1862, 2013. © 2013 Wiley Periodicals, Inc.